Knowledge, attitude and stigma experienced by leprosy patients in tribal concentrated Bastar district of Chhattisgarh, India (2013-2023) - Swapan Kumar Kolay; Samiran Bisai; Ranabir Pal; Pradip Kumar Mohanta; Debabrata Sarbapalli (Turkish Journal of Public Health, 2016)
Objective: To study leprosy patients in tribal concentrated Bastar district of Chhattisgarh, India in terms of their knowledge, attitudes and the stigma they have experienced. Method: This cross-sectional study included 101 registered Leprosy patients, in a single leprosy treatment centre between April, 2012 - June, 2013. The data collection tool (a pre tested close-ended questionnaire) was based on leprosy related socio-demographic variables, knowled geregarding different kinds of problems and issues experienced by the patients/participants. The investigators collected the data in face to face interviews and house hold visit. Results: Overall the majority of the respondents (85.1%) were between 16 and 60 years of age. 74.3% were males, 80.2% were married, and 54.5% were literate. The majority (67.3%) articulated positive knowledge about transmission of the disease, 75.3% knew that numbness of hands is an early symptom, 88.12% that it is curable, 91.1% had untreated deformities. Experiences reported included disturbed marital relationships (90.1%) or social life (94.1%), loss of employment (54.5%), isolation with the sitation to talk to people (29.7%), family members not sharing food (94.1%); being forced to leave the family (54.45%). Health education interventions improved the knowledge of 91.1% of participants. Multi-Bacillary leprosy was higher in newly registered cases with higher disabilities in the hands and feet (60.4%), eyes (29.7%). 9.9% of WHO grade-2 disabilities were due to a delayed diagnosis. 67.5% of the patients/participants with some form of disability had experienced a delay in diagnosis up to 12 months. Conclusion: The study noted that the tribal people were affected by leprosy not only in terms of the physical problems, but also by the stigmatization that affects their social participation. These need to be addressed by the progress of the national leprosyp rogram. Keywords: Leprosy, social stigma, disability grading, India